Induction of chromosomal damage in exfoliated buccal and nasal cells of road markers. Issue 17 (2nd September 2019) - Wultsch, Georg; Nersesyan, Armen; Kundi, Michael; Al-Serori, Halh; Knasmüller, Siegfried
ABSTRACT: Road markers are exposed to various chemicals and particles. The aim of this study was to determine whether road worker exposure induceschromosomal damage which is indicative for increased cancer risks. Micronucleus (MN) cytome assays were thus conducted with exfoliated nasal and buccal cells collected from 42 workers and 42 matched controls. The frequencies of MN (reflecting chromosomal aberrations), nuclear buds (NBuds; reflecting gene amplifications) and binucleated cells (BN; reflecting disturbed mitosis) were scored. Further, the rates of nuclear anomalies indicative of acute cytotoxicity (condensed chromatin, karyorrhexis, karyolysis, pyknosis) were evaluated. Data demonstrated marked induction of MN, NBuds, and BN by 1.34-fold, 1.24-fold and 1.14-fold in buccal cells. In nasal cells, only MN frequencies were elevated, 1.23-fold. These effects were paralleled by increased rates of condensed chromatin, karyorrhexis and karyolysis in both cell types. The effects were more pronounced in individuals who had worked for more than 10 years while smoking did not produce synergistic responses. This is the first investigation concerning the induction of genetic damage in road markers and the results are suggestive for enhanced cancer risks. It is conceivable that exposure to silica dust (known to induce cancer and genetic damage) and/or benzoyl peroxide which forms reactive radicals may be associated with the observed genetic damage in road workers. Further investigations of the cancer risks of these workers are warranted.